The Effect Of Administrative Empowerment - Seffahlou, Rachid (جامعة الوادي University of Eloued, 2025)
This study aimed to find out the effect of administrative empowerment in developing organizational citizenship behavior among a sample of administrators at the Algerian Water Corporation in Ain Defla. The questionnaire was adopted as the main tool for obtaining the necessary data, which was distributed to an item size of 50. The data was analyzed using a set of statistical methods by adopting the Social Statistical Packages Program (SPSS V23). The study resulted in no statistically significant effect of the dimensions of administrative empowerment on developing organizational citizenship behavior. The study recommended the necessity of changing work methods, programming training courses for employees, motivating them, and paying attention to consolidating the concept of organizational citizenship behavior and highlighting its positive effects on the individual, the group, and the institution. The study recommended the necessity of changing work methods, programming training courses for employees, motivating them, paying attention to consolidating the concept of organizational citizenship behavior, highlighting its positive effects and delegating greater powers to administrators, and listening to their ideas and suggestions.
The effect of administrative empowerment on the development of organizational citizenship behaviour (field study on a sample of employees at the Algerian Water Corporation in Ain Defla)
Keywords: administrative empowerment; development; citizenship behavior; competitive capabilities; Human resources .